Investigation of a single-layer EBC deposited on SiC/SiC CMCs: Processing and corrosion behaviour in high-temperature steam. Issue 8 (July 2019) - Al Nasiri, N.; Patra, N.; Pezoldt, M.; Colas, J.; Lee, W.E.
Abstract: Two rare earth monosilicates (Yb2 SiO5, and Lu2 SiO5 ) were deposited using a low-cost coating application method to produce a single-layer coating. RE- oxides slurries were dip coated on oxidised CMC samples and subsequently heat treated at high temperature to ensure reaction between SiO2 and RE-oxides to form the RE-monosilicate. A single, continuous, homogeneous thick coating of 25 μm was obtained. X-ray diffraction (XRD) confirmed formation of, RE-monosilicates in Yb and Lu silicate systems. Coated samples were exposed to 90% H2 O static steam environment at 1350 °C for 25, 50, 100, and 150 h. Scanning Electron Microscopy (SEM) indicated that both coatings adhered strongly to the substrate. Coating thickness reduced from 22 μm to 11 μm for Yb-coating and 13 to 4 μm for Lu-coating with increasing corrosion time from 25 to 150 h, however there was no significant attack of the CMC for all steam exposure times.